Mapping the current trends and hotspots of extracellular vesicles in Alzheimer's disease: a bibliometric analysis - Xing, Xiaolian; Liu, Hongwei; Zhang, Minheng; Li, Yang (Frontiers in Aging Neuroscience, 2024)
BackgroundExtracellular vesicles (EVs) have garnered significant attention in Alzheimer's disease (AD) research over the past decade, largely due to their potential in diagnostics and therapeutics. Although the investigation of EVs in AD is a relatively recent endeavor, a comprehensive bibliometric analysis of this rapidly growing field has yet to be conducted.MethodsThis study aims to elucidate and synthesize the relationship between EVs and AD, offering critical insights to guide future research and expand therapeutic possibilities. Over the past 10–15 years, substantial progress has been made in this domain. Through bibliometric techniques, this analysis assesses research performance by examining scientific publications and metrics, including productivity indicators, impact measurements, data mining, and visualization tools.ResultsA total of 602 publications were analyzed using various online platforms for bibliometric analysis. Notably, the number of publications began to increase rapidly in 2018, with China and the United States emerging as leaders in this research area. The National Institute on Aging produced the highest number of publications among institutions. The Journal of Molecular Sciences and the Journal of Biological Chemistry were the most prolific and most frequently cited journals, respectively. Among individual contributors, Dimitrios Kapogiannis was identified as the most productive author, while Edward J. Goetzl was the most co-cited. The most prevalent keywords included “neurodegenerative diseases,” “exosomes,” “blood biomarkers,” “amyloid beta,” “microglia,” and “tau protein.” Current research hotspots involve microRNA dysregulation, oxidative stress, carboxyl-terminal fragments, small EVs, and mesenchymal stem cell-derived EVs, indicating key areas for future research.ConclusionResearch on microRNA dysregulation, oxidative stress, carboxyl-terminal fragments, small EVs, and mesenchymal stem cell-derived EVs represents a critical frontier in the study of Alzheimer's disease. The role of EV-mediated neuroinflammation in AD is a focal point of ongoing investigation and will likely shape future developments in the field.